Dyspnea and perfusion defects (V/Q scan) are common after an acute pulmonary embolus whereas chronic thromboembolic pulmonary hypertension (CTEPH) is a rare sequele. (3rd October 2022) - Andersson, T; Nilsson, L; Larsen, F; Carlberg, B; Soderberg, S
Abstract: Introduction: Acute pulmonary embolism (PE), a common disease with substantial morbidity and mortality. Many previous studies have focused on the short-term consequences after an acute PE, but less attention has been directed to the long-term effects of a PE. The most feared complication is chronic thromboembolic pulmonary hypertension (CTEPH), with reported incidence rates ranging from 0.6 to 4.8%. Even though CTEPH is a rare complication after PE, dyspnea and functional impairment are common complaints, and a syndrome named PPES (post-PE-syndrome) has been suggested. The aim of this study was to follow a large national-wide cohort of post-PE-patients and to gather information regarding long-term symptoms and to determine the prevalence of CTEPH. Patients and methods: We identified all patients diagnosed with acute PE in 2005 (ICD-10-SE: I26.0 and I26.9) that were registered in the Swedish National Patient Register (NPR), which has nearly 100% coverage. In 2007, all surviving individuals were invited to participate by letter. They were asked to complete a questionnaire regarding symptoms and risk factors for long-term sequele including CTEPH. Individuals who reported dyspnea or had known risk factors for CTEPH were invited to a follow-up with blood tests (NT-pro-BNP) and pulmonary scintigraphy. If any perfusion defects were detected, an echocardiography was performed. If signs of pulmonary hypertension, a referral was done to the regional PAH-center. Results: In 2005, 5793 unique patients were admitted with a PE diagnosis in Sweden. Of those, 3510 were still alive in 2007, and 3226 individuals were contacted and asked to complete the questionnaire. Altogether 2105 (65%) individuals returned the questionnaire, and 53% reported dyspnea and 15% were asymptomatic but had risk factors for CTEPH. Altogether 944 individuals were referred for further follow-up including a recommendation to perform a V/Q-scan. Altogether 530 V/Q-scans were performed and 44% showed perfusion defects, whereof 85% had an echocardiography. Twenty-seven % of them registered a systolic right ventricular pressure of at least 30 mmHg. Referrals resulted in 6 cases with proved CTEPH. In parallel, 10 patients with CTEPH diagnosed before 2005 were detected, and 8 patients were diagnosed after 2005 and outside the study.Altogether 24 patients with CTEPH were thus identified and the cumulative incidence of CTEPH ranged between 0.7 and 1.2%. Conclusion: Dyspnea is common after an acute PE and over 40% of them have perfusion defects on a V/Q scan, suggesting the presence of a post PE-syndrome (PPES). The incidence of CTEPH is however low. More research is needed to better define PPES. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Actelion PharamceuticalsSwedish Heart and Lung Foundation